2023
DOI: 10.3389/fneur.2023.1155669
|View full text |Cite|
|
Sign up to set email alerts
|

The longitudinal progression of autonomic dysfunction in Parkinson's disease: A 7-year study

Abstract: BackgroundAutonomic dysfunction, including gastrointestinal, cardiovascular, and urinary dysfunction, is often present in early Parkinson's Disease (PD). However, the knowledge of the longitudinal progression of these symptoms, and the connection between different autonomic domains, is limited. Furthermore, the relationship between the presence of autonomic symptoms in early-stage PD and olfactory dysfunction, a possible marker of central nervous system involvement, has not been fully investigated.ObjectivesWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…[29] In current study, we found autonomic dysfunction was positively associated with HY stages and UPDRS-III scores, which was in agreement with previous studies showing that autonomic dysfunction was associated with faster motor progression. [9] We found autonomic symptoms were positively associated with ESS scores, which was supported by a recent study showing that more severe EDS in PD patients was in parallel with more worsened autonomic symptoms. [41] A previous study showed that female sex, high HY stage, high UPDRS total and subtotal scores, and cognitive decline were significantly associated with depressive symptoms.…”
Section: Autonomic Dysfunction and Clinical Symptoms In Pdsupporting
confidence: 87%
See 1 more Smart Citation
“…[29] In current study, we found autonomic dysfunction was positively associated with HY stages and UPDRS-III scores, which was in agreement with previous studies showing that autonomic dysfunction was associated with faster motor progression. [9] We found autonomic symptoms were positively associated with ESS scores, which was supported by a recent study showing that more severe EDS in PD patients was in parallel with more worsened autonomic symptoms. [41] A previous study showed that female sex, high HY stage, high UPDRS total and subtotal scores, and cognitive decline were significantly associated with depressive symptoms.…”
Section: Autonomic Dysfunction and Clinical Symptoms In Pdsupporting
confidence: 87%
“…[58] In addition, it has been shown that more severe autonomic dysfunction at baseline was associated with future worse olfaction loss and greater overall disease burden. [9] Moreover, the severity of autonomic symptoms was independently associated with impairments in activities of daily living and health-related quality of life. [6, 10] Therefore, the clinical diagnosis and treatment of autonomic dysfunction is extremely important in PD management.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 , 29 , 30 The accumulation of α‐synuclein in the ENS has been found to correlate with cell death in the autonomic nervous system and is suggested to lead to autonomic dysfunction in the GI domain. 27 Based on the ENS‐first etiology of PD (the initial α‐synuclein pathology within the ENS), 31 researchers proposed that the pathologic change first happens in the GI system and then ascends through the vagus nerve to the brainstem which is closely related to the formation of hallucinations. 9 , 28 , 32 , 33 , 34 Our findings provide more evidence to support the theory that degeneration of the brainstem is associated with psychosis in PD, and autonomic dysfunction and pRBD in PD may be driven by similar neurobiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…GI autonomic dysfunction has been proposed as a prodromal non‐motor symptom of PD. Evidence has pointed to abnormal α‐synuclein accumulating not only in the brain but also in the enteric nervous system (ENS) 27–30 . The accumulation of α‐synuclein in the ENS has been found to correlate with cell death in the autonomic nervous system and is suggested to lead to autonomic dysfunction in the GI domain 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation